Advanced process integration for supercritical production of biodiesel: Residual waste heat recovery via organic Rankine cycle (ORC). (February 2021) - Aboelazayem, Omar; Gadalla, Mamdouh; Alhajri, Ibrahim; Saha, Basudeb
Abstract: Biodiesel production using supercritical methanolysis has received immense interest over the last few years. It has the ability to convert high acid value feedstock into biodiesel using a single-pot reaction. However, the energy intensive process is the main disadvantage of supercritical biodiesel process. Herein, a conceptual design for the integration of supercritical biodiesel process with organic Rankine cycle (ORC) is presented to recover residual hot streams and to generate electric power. This article provides energy and techno-economic comparative study for three developed scenarios as follows: original process with no energy integration (Scenario 1), energy integrated process (Scenario 2) and advanced energy integrated process with ORC (Scenario 3). The developed integrated biodiesel process with ORC resulted in electric power generation that has not only satisfied the process electric requirement but also provided excess power of 257 kW for 8, 000 tonnes/annum biodiesel plant. The techno-economic comparative analysis resulted in favouring the third scenario with 36% increase in the process profitability than the second scenario. Sensitivity analysis has shown that biodiesel price variation has significant effect on the process profitability. In summary, integrating supercritical biodiesel production process with ORC appears to be a promising approach for enhancing the process techno-economic profitability and viability. Highlights: Residual hot streams in supercritical biodiesel process are valorised into electric energy via ORC. Supercritical biodiesel process integration with ORC provides self-sufficiency in electric energy. Three scenarios for the supercritical biodiesel production process were compared for techno-economic viability. The developed integrated biodiesel process with ORC is the optimal techno-economic scenario.